Geomorphologische Kartographie in der Bundesrepublik Deutschland: Normung und Weiterentwicklung - Spönemann, Jürgen; Lehmeier, Friedmut (ERDKUNDE, 1989)
After a short recapitulation of the essentials of geomorphological mapping a critical analysis of the cartographic concept of a modern geomorphological map of the Federal Republic of Germany (“Geomorphologische Karte der Bundesrepublik Deutschland - GMK) is given. In this context the presentation of morphographic details, especially slope curvature, is discussed. In principal, a dual-sheet system of geomorphological mapping is required. Following the proposal of Hagedorn & Lehmeier (1983), and completing their morphogenetic version, a corresponding morphographic mapping method is presented. Its aim is to connect the effect of plastic shading with detailed morphometric description. Contours and selected topographic elements serve as the map base. As general form characteristics the slope categories of inclination and vertical curvature are displayed by raster screens, combining grey tone values and different raster types. In addition, slope discontinuities and special form elements are considered. Emphasizing culmination lines and points, higher ranking land forms will be expressed. By differentiation of the referring symbols the relative height of ridges and hills is to be considered. Giving a precise picture of the relief, the morphographic map meets the requirements of environmental planning, and due to the restricted use of symbols and colours it can serve as a base map for further thematic information.